Development of Interactive Learning Media Edugame using ADDIE Model - Fadhli Ranuharja; Ganefri Ganefri; Bayu Ramadhani Fajri; Febri Prasetya; Agariadne Dwinggo Samala (Universitas Negeri Padang, 2021)
In line with the district development program of Dharmasraya regency, namely the Dharmasraya Smart City Program and the implementation of Dharmasraya Smart Education, Edugame is currently one of the favourite innovations being used in the teaching and learning process for the primary school students. This study was aimed at creating a learning innovation using Edugame as a media for conveying information to students as well as inviting students to play. In addition, the approach method used was in the form of media development using the ADDIE (Analysis Design Develop Implementation and Evaluation) development method. This development method was started by conducting the field observations, then designing the Edugame interface to evaluate the shortcomings of the Edugame. From the results of the whiteboard test, it was proven that this application had succeeded in delivering learning materials to primary school students of SDN 08 Pulau Punjung, Dharmasraya Regency, West Sumatra. In sum, the teachers are assisted by the Edugame since the students learn independently to explore each Edugame and try to get the highest score. Keywords: Learning Media; Edu-Game; Learning Innovation; ADDIE.